Reduction of tetrachloroaurate (III) at boron-doped diamond electrodes: Gold deposition versus gold colloid formation - Holt, K; Sabin, G; Compton, R; Foord, J; Marken, F (2002)
Tetrachloroaurate(III) dissolved in dilute aqueous aqua regia is electrochemically reduced at boron-doped diamond electrodes to form gold metal. The reduction process is studied by voltammetric, SEM, and XPS techniques. Both the deposition of gold and the anodic stripping process are detected. The ratio of cathodic to anodic charge or stripping efficiency, Qanodic/Qcathodic, is shown to depend on the concentration of AuCl4- and on the pretreatment of the boron-doped diamond electrode surface. Cathodic pretreatment of the boron-doped diamond electrode considerably increases the rate for both deposition and stripping. In the presence of power ultrasound emitted from a glass horn system (24 kHz, 8 Wcm-2) the current associated with the reduction of AuCl4- is considerably enhanced and two components in the mass transport controlled limiting current are identified as (i) the deposition of gold onto the boron-doped diamond and (ii) the formation of colloidal gold.